Faith and fakes – dealing with critical information in decision analysis. Issue 1 (2nd January 2019) - Nielsen, Linda; Tølbøll Glavind, Sebastian; Qin, Jianjun; Faber, Michael H.
ABSTRACT: Decision making subject to uncertain information, whether fake or factual, in the context of management of socio-technical systems, is critically discussed from both philosophical and operational perspectives. In dealing with possible fake, incorrect and/or factual information we take the perspective that any information utilised as basis for supporting decisions, has to be dealt with in exactly the same manner – in accordance with Bayesian decision analysis. The important issue is to identify and model the scenarios through which information may cause adverse consequences and to account for their potential effects. To this end we first provide a mapping of how information affects the decision making context and a categorisation of causes for information leading to adverse consequences. Secondly, we introduce a decision analytical framework aiming to optimise decision alternatives for managing systems including not only one possible system model but a set of different possible system models. As a means for assessing the benefit of collecting additional information, we utilise Value of Information analysis from Bayesian decision analysis. Finally, a principal example is provided which illustrates selected aspects of how possibly fake information affects decision making and how it might be dealt with.